Thermomechanical behavior of aeronautic structural carbon epoxy composite submitted to a laser irradiation. (20th May 2016) - Lacroix, F.; Allheily, V.; Diener, K.; Eichhorn, A.; Gillet, M.; L'Hostis, G.
Abstract: In the frame of a study on aeronautic composite structures submitted to laser irradiation, we have assessed the thermo mechanical behavior of carbon epoxy composite. The carbon fibers withstand ∼1 kW/cm 2 power density but the matrix is completely burned. At higher power densities, an ablation of the fibers is observed. The behavior of the matrix composition which included epoxy based resin and a lot of additives, plasticizer, delaying agents, and surfactants …, has also featured some internal ebullition phenomena. Such ebullition has been attributed to the additives thanks to a comparative experimental study on pure epoxy resin and matrix behavior. The resin is optically semi-transparent at the laser wavelength and shows an ablative behavior. The matrix is an optically diffused media due to the inclusions of micro bubbles of additives within the resin. These inclusions which have lower degradation temperature compared to the epoxy resin one induced an internal ebullition inside the epoxy based matrix. These internal ebullition phenomena create local overpressures speeding up the delaminating phenomena of the composite. We have studied the thermo-mechanical behavior of our samples. We have demonstrated a simple linear dependence of the mechanical degradation of carbon epoxy composite material and the laser deposed energy.